Students’ Smartphone Use and Reading Interest Beyond Class Hours: Qualitative Study of Bosowa University Students - Nur Khaliva Dwiva; Sri Wahyuni J; Chelsy Julianti Ippin; Restu Januarty Hamid; Achmad Fajar Muhammad (International Journal of Research in Education, 2026)
The rapid development of digital technology has influenced learning behavior in higher education, particularly in smartphone usage and reading activities. This study aimed to explore English Education students’ experiences and perceptions of smartphone usage and reading interest outside classroom hours at Bosowa University. The study employed a qualitative descriptive design involving 10 participants selected through purposive sampling. Data were collected through open-ended questionnaires and follow-up interviews and were analyzed thematically through data reduction, data display, and conclusion drawing based on Miles, Huberman, and Saldaña’s framework. The findings revealed that most participants spent more time using smartphones for entertainment purposes such as social media, short videos, and online communication than for academic reading activities. Participants also preferred instant and visually attractive digital content because it was perceived as more practical and enjoyable than reading lengthy academic texts. Excessive smartphone usage was perceived to contribute to students’ reading habits, concentration, time management, and motivation to engage in literacy activities outside classroom hours. In addition, limited literacy support within students’ social environments contributed to low reading interest. The study concludes that excessive smartphone usage for entertainment purposes may contribute to lower reading engagement and weaker academic literacy habits. Therefore, balanced smartphone usage and stronger literacy support are needed to encourage more productive reading activities outside classroom learning.